600,000 hectares of rice planted earlier in Vietnam to avoid risk of salinity intrusion from the 2019 El Niño - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Based on directives issued by the Vice Minister of the Ministry of Agriculture and Rural Development (MARD) and the Department of Crop Production, the rice planting calendar in the Mekong River Delta was adjusted to avoid salinity intrusion brought by the 2019 El Niño.